Risk factors for rebleeding of aneurysmal subarachnoid hemorrhage: a meta-analysis. - Chao Tang; Tian-Song Zhang; Liang-Fu Zhou (PLoS ONE, 2014)
Background Rebleeding is a serious complication of aneurysmal subarachnoid hemorrhaging. To date, there are conflicting data regarding the factors contributing to rebleeding and their significance. Methods A systematic review of PubMed and Embase databases was conducted for studies pertaining to aneurysmal subarachnoid hemorrhage (aSAH) and rebleeding in order to assess the associated risk factors. Odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were estimated from fourteen studies comprised of a total of 5693 patients that met the inclusion criteria. Results Higher rebleeding rates were observed < 6 h after the initial aSAH (OR  = 3.22, 95% CI  = 1.46-7.12), and were associated with high systolic blood pressure (OR  = 1.93, 95% CI  = 1.31-2.83), poor Hunt-Hess grade (III-IV) (OR  = 3.43, 95% CI  = 2.33-5.05), intracerebral or intraventricular hematomas (OR  = 1.65, 95% CI  = 1.33-2.05), posterior circulation aneurysms (OR  = 2.15, 95% CI  = 1.32-3.49), and aneurysms >10 mm in size (OR  = 1.70, 95% CI  = 1.35-2.14). Conclusions Aneurysmal rebleeding occurs more frequently within the first 6 hours after the initial aSAH. Risk factors associated with rebleeding include high systolic pressure, the presence of an intracerebral or intraventricular hematoma, poor Hunt-Hess grade (III-IV), aneurysms in the posterior circulation, and an aneurysm >10 mm in size.